Psychological distress : symptoms, causes, and coping - Ohayashi, Hayate; Yamada, Shuji (Editor of Psychological distress) (Psychology of emotions, motivations, and actions series., 2012)
Psychological distress is a term used to describe the general psychopathology of an individual with a combination of depressive symptoms, anxiety and perceived stress. In this book, the authors have gathered and present topical research in the study of the symptoms, causes and coping mechanisms relating to psychological distress. Included in this compilation are topics corresponding to mitigating adverse school experiences and psychological distress with parental support; psychological distress in an oncological context; screening for psychological distress in clinical practice; and, the Kessler 10 (K10) psychological distress scale and psychological distress in the military.